Teaching reading in grade 4 Namibian classrooms : a case study - Mutenda, Josephine (Rhodes University, Faculty of Education, Department of Education, 2008)
Literacy is currently a topic of great concern in Namibia. Learners in this country have difficulty in reading and writing, and are often functionally illiterate. This study focuses on the beliefs, experiences and practices of teachers of reading in English to second language learners in Grade 4. Grade 4 is the transitional grade from mother tongue to English as the medium of instruction. The switch to English makes teaching reading in that language especially challenging. The study is structured according to the case study mode of enquiry, with the target respondents comprising Grade 4 teachers. Classroom observation, interviews and document analysis were used as means of collecting data. The main findings revealed that beliefs and experience had an impact on the way in which reading was taught in this study. It emerged that the teachers' childhood experiences of literacy and learning to read are perpetuated in their beliefs, their attitudes, their basic conceptualization of reading and their current practices, all of which directly affect the children in their classes. Although the teachers' professional training also had some influence on their teaching methods, neither of the two teachers interviewed had received much in-service support on how to teach reading, and they depended to a large extent on their recall of how they had learned to read themselves. Both teachers were taught in a traditional, teacher-centered way, involving phonics, rote-learning and drilling. Because they see themselves as competent readers, they believe that these approaches were effective and worth sustaining. Tentative recommendations arising from analysis of the data indicate possible areas for improvement in the teaching of reading, and offer guidelines to help teachers cope with the challenge.
Keywords: Literacy -- Study and teaching (Elementary) -- Namibia; English language -- Study and teaching (Elementary) -- Namibia; Reading (Elementary) -- Namibia; Second language acquisition